(untitled) (Annals of Medical Research, 2022)
Aim: The mandible is one of the most frequently fractured bones of the maxillofacial region. In this study, it was aimed to contribute to the literature by examining the demographic data, etiological causes, fracture types and treatment methods of our patients with mandible fractures. Materials and Methods: The data of 138 patients who were hospitalized for mandibular fracture in our plastic surgery clinic between 2010 and 2022 were retrospectively analyzed. Demographic and surgical data were evaluated. Results: 196 fractures of 138 patients were operated for mandibular fractures. The mean age of the patients was 30.5±18 (1-81) years. Twenty-five (18.1%) were female, 113 (81.9%) were male. The most common cause was falls in 70 patients (50.7%), and the second most common cause was motor vehicle crash (32.6%). Most common fracture in the mandible was parasymphysis and second most common fracture site was the body region with 37 (18.8%) fractures. Conclusion: Fractures of the mandible are frequently encountered in patients presenting with trauma. It is usually seen in male patients in their 30s, and parasymphysis is the most common site. Other facial fractures and general body trauma that may accompany the patient should be considered while evaluating the patient. Thanks to the measures taken, motor vehicle crash, which used to be the most common etiological cause, have decreased. The number of these traumas can be reduced with new measures for etiology.